Evidence for the use of complementary and alternative medicines during fertility treatment: a scoping review - Skye A. Miner; Stephanie Robins; Yu Jia Zhu; Kathelijne Keeren; Vivian Gu; Suzanne C. Read; Phyllis Zelkowitz (BMC, 2018)
Abstract Background Complementary and alternative medicines (CAM) are sometimes used by individuals who desire to improve the outcomes of their fertility treatment and/or mental health during fertility treatment. However, there is little comprehensive information available that analyzes various CAM methods across treatment outcomes and includes information that is published in languages other than English. Method This scoping review examines the evidence for 12 different CAM methods used to improve female and male fertility outcomes as well as their association with improving mental health outcomes during fertility treatment. Using predefined key words, online medical databases were searched for articles (n = 270). After exclusion criteria were applied, 148 articles were analyzed in terms of their level of evidence and the potential for methodological and author bias. Results Surveying the literature on a range of techniques, this scoping review finds a lack of high quality evidence that complementary and alternative medicine (CAM) improves fertility or mental health outcomes for men or women. Acupuncture has the highest level of evidence for its use in improving male and female fertility outcomes although this evidence is inconclusive. Conclusion Overall, the quality of the evidence across CAM methods was poor not only because of the use of research designs that do not yield conclusive results, but also because results were contradictory. There is a need for more research using strong methods such as randomized controlled trials to determine the effectiveness of CAM in relation to fertility treatment, and to help physicians and patients make evidence-based decisions about CAM use during fertility treatment.